2022
DOI: 10.3390/life12071021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Hormonal Regulation in Rice Seed Germination

Abstract: Seed germination is a critical stage during the life cycle of plants. It is well known that germination is regulated by a series of internal and external factors, especially plant hormones. In Arabidopsis, many germination-related factors have been identified, while in rice, the important crop and monocot model species and the further molecular mechanisms and regulatory networks controlling germination still need to be elucidated. Hormonal signals, especially those of abscisic acid (ABA) and gibberellin (GA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 140 publications
0
6
0
1
Order By: Relevance
“…Determination of seed dormancy and the optimal moment to initiate germination is critical for improving plant livelihood and avoiding potential threats in the first stages of seedling development. It is well established that GA is the main hormone involved in seed dormancy breakdown, and the ABA/GA balance is the major regulator of seed dormancy and germination in wheat [ 178 ] and rice [ 179 ], with high GA content leading to decreased dormancy. In rice, the interplay between GA and BRs through the activity of LEA genes has also been shown to influence dormancy [ 180 ].…”
Section: Seed Germinationmentioning
confidence: 99%
“…Determination of seed dormancy and the optimal moment to initiate germination is critical for improving plant livelihood and avoiding potential threats in the first stages of seedling development. It is well established that GA is the main hormone involved in seed dormancy breakdown, and the ABA/GA balance is the major regulator of seed dormancy and germination in wheat [ 178 ] and rice [ 179 ], with high GA content leading to decreased dormancy. In rice, the interplay between GA and BRs through the activity of LEA genes has also been shown to influence dormancy [ 180 ].…”
Section: Seed Germinationmentioning
confidence: 99%
“…S1) suggested that 19 (1, 3-8, 18, 20, 22, 23, 26, 27, 32, 33, 35, 37, 43, 55) were phenolic acids, 18 (2, 9-11, 13, 15, 16, 21, 29, 34, 40, 50, 51, 57, 59, 60, 63, 64) were isoflavones, three (12,14,47) were flavones, and two (19,24) were dihydroflavonoids. Besides, 18 flavonol glycosides were found, distributed as one myricetin-3-O-glycoside (25), nine kaempferol-3-Oglycosides (28,41,42,44,46,48,53,54,56), three quercetin-3-O-glycosides (31,39,45), one kaempferol-3,7-Odiglycoside (52), and four flavonol glycosides to which a type could not be assigned (17,30,36,49). Also, three flavonol aglycones were found: myricetin (58), quercetin (62), and kaempferol (66) to two chalcones (38,61), and one non-identified type of phenolic compound (65).…”
Section: Phenolic Compounds Of Seeds Soaked Seeds and Sproutsmentioning
confidence: 99%
“…These glycosides, besides diversifying the phenolic composition of sprouts, can play protective roles as antioxidants, as this activity has been well-recognized for them (3). In addition, these types of glycosides also can change the hydrophilicity and chemical stability of receptor molecules, improving the transportation of plant hormones (40) and contributing to the adequate hormone balance, which is needed for germination (41).…”
Section: Phenolic Composition Of Sproutsmentioning
confidence: 99%
“…After-ripening terjadi karena adanya ketidakseimbangan hormon khususnya ABA dan GA 3 (Zuo dan Xu, 2020). Kedua hormon ini berkaitan erat dengan aktivitas enzim-enzim yang berperan dalam proses perkecambahan benih (Joshi, 2018;Gong et al, 2022). GA 3 berperan dalam aktivasi enzim-enzim hidrolisis yang terjadi setelah imbibisi, dan akan meningkatkan aktivitas metabolisme lainnya, seperti respirasi (Guzmán-Ortiz et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified